THE EFFECT OF CIRC MODEL ON STUDENT LEARNING OUTCOMES FOR ELEMENTARY SCHOOL - Reinita; Mifthahul Jannah (Jurnal Cakrawala Pendas, 2023)
This research is motivated by learning that has not used innovative learning models so that students are less active in learning, not maximal cooperation between students in understanding learning materials. This resulted in student learning outcomes in integrated thematic learning still being low. The research’s goal is to see how the Cooperative Integrated Reading and Composition type cooperative model affects student learning results in class V Cluster I, IV Jurai District. The Cooperative Integrated Reading and Composition (CIRC) model approach combines reading and writing assignments. Cooperative learning is a sort of group instruction that allows students more control over their learning and teams, fostering an interdependence that promotes friendly social interaction and supports learning. Each activity in group interaction is carried out using a set of procedures, which include teacher presentations, group practice, individual practice, peer review, additional practice, and testing. Employed a non-equivalent control group design as a quasi-experimental design. Sampling was carried out by purposive sampling technique. Class VA has designated the experimental class, whereas class VB was designated the control class. The t-test revealed that tcount is 2,399 and ttable at the 95 percent confidence level, with a significant level (α) of 0.05, is 2.045. Because tcount >  ttable (2,399 > 2,045), we can assume that H1 is acceptable. Based on the research results, by testing the hypothesis using the t test, H1 is accepted. It can be concluded that employing the Cooperative Integrated Reading and Composition (CIRC) model approach has a substantial impact and significant effect on student learning outcomes in Elementary School. Penelitian ini dilatarbelakangi pembelajaran yang belum menggunakan model pembelajaran inovatif sehingga peserta didik kurang aktif dalam pembelajaran, belum maksimalnya kerja sama antar peserta didik dalam memahami materi pembelajaran. Hal ini mengakibatkan hasil belajar peserta didik pada pembelajaran tematik terpadu masih rendah. Tujuan penelitian adalah untuk melihat bagaimana pengaruh model kooperatif tipe Cooperative Integrated Reading and Composition terhadap hasil belajar siswa kelas V Gugus I IV Kecamatan Jurai. Pendekatan model Cooperative Integrated Reading and Composition (CIRC) memadukan tugas membaca dan menulis. Pembelajaran kooperatif adalah semacam instruksi kelompok yang memungkinkan siswa lebih mengontrol pembelajaran dan tim mereka, menumbuhkan saling ketergantungan yang mempromosikan interaksi sosial yang ramah dan mendukung pembelajaran. Setiap kegiatan dalam interaksi kelompok dilakukan dengan menggunakan seperangkat prosedur, yang meliputi presentasi guru, praktik kelompok, praktik individu, peer review, praktik tambahan, dan tes. Mempekerjakan desain kelompok kontrol yang tidak setara sebagai desain kuasi-eksperimental. Pengambilan sampel dilakukan dengan teknik purposive sampling. Kelas VA ditetapkan sebagai kelas eksperimen, sedangkan kelas VB ditetapkan sebagai kelas kontrol. Hasil uji t diketahui thitung sebesar 2,399 dan ttabel pada tingkat kepercayaan 95 persen, dengan taraf signifikan (α) 0,05 sebesar 2,045. Karena t hitung > ttabel (2,399 > 2,045), maka dapat diasumsikan bahwa H1 diterima. Dapat disimpulkan bahwa penerapan model Cooperative Integrated Reading and Composition (CIRC) memiliki pengaruh yang cukup besar dan signifikan terhadap hasil belajar siswa di Sekolah Dasar.